Advanced, efficient primary beam modeling for the Murchison Widefield Array radio telescope - Wayth, Randall; Colegate, T.; Sokolowski, Marcin; Sutinjo, Adrian; Ung, D. (2016)
The Murchison Widefield Array (MWA) radio telescope is the precursor instrument to the future international SKA-Low radio telescope. The MWA is pursuing a number of ambitious key science programs, the most challenging of which is to make the first detection of the faint signal from the early universe. Fundamental to achieving the very high fidelity imaging required for MWA key science programs is an accurate and flexible model of the MWA's primary beam. This work will present an advanced, frequency dependent, fully general model of the MWA primary beam. The model has been implemented as a set of spherical harmonics such that the beam response can be predicted anywhere on the sky without the need for interpolation.